Consumer Legal Protection for Overclaimed Skincare Products - Awalin, Hanif Fil’; Hutabarat, Sylvana Murni Deborah (Universitas Muhammadiyah Sumatera Utara, 2025)
This research focuses on the legal protection of consumers who are harmed by the practice of overclaims on skincare products. The rapidly growing skincare industry in Indonesia raises new problems, namely promotions that contain excessive claims, thus misleading consumers. This has a negative impact on public trust and poses a health risk. The research uses a juridical-normative method with a statutory approach, examining regulations such as the Consumer Protection Law No. 8 of 1999 and BPOM Regulation No. 12 of 2023. The analysis was conducted to understand the role of BPOM in supervision and to identify regulatory challenges in overcoming overclaim practices. This research aims to provide recommendations to regulators, producers, and consumers to create a transparent and safe skincare market